1999
DOI: 10.1259/bjr.72.863.10700827
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic contrast enhanced magnetic resonance scanning as a predictor of response to accelerated radiotherapy for advanced head and neck cancer.

Abstract: Tumour perfusion has been assessed in patients with advanced head and neck cancer using dynamic contrast enhanced MRI prior to and at completion of accelerated radiotherapy, and related to local tumour control. Sequential MRI scans, at 3 s intervals after intravenous injection of gadolinium using a dynamic scan sequence through a tumour region of interest (ROI), were performed in 13 patients with advanced head and neck cancer before and on completion of radiotherapy. The scans have been analysed in terms of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
55
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(58 citation statements)
references
References 9 publications
2
55
0
1
Order By: Relevance
“…9,10 Early proponents of perfusion studies have also demonstrated in a clinical setting that semi-or quantitatively estimated tumor perfusion might predict the outcome after definitive radiation therapy. 11,12 A recent study also reported the significant predictive value of PCT studies in a small patient population treated with surgery and adjuvant chemoradiation. 13 However, to the best of our knowledge, there is no large-scale study examining the longterm predictive value of baseline PCT studies in patients treated with neoadjuvant chemoradiation or chemoradiation with curative intent.…”
mentioning
confidence: 93%
“…9,10 Early proponents of perfusion studies have also demonstrated in a clinical setting that semi-or quantitatively estimated tumor perfusion might predict the outcome after definitive radiation therapy. 11,12 A recent study also reported the significant predictive value of PCT studies in a small patient population treated with surgery and adjuvant chemoradiation. 13 However, to the best of our knowledge, there is no large-scale study examining the longterm predictive value of baseline PCT studies in patients treated with neoadjuvant chemoradiation or chemoradiation with curative intent.…”
mentioning
confidence: 93%
“…Patients with HNSCC with elevated tumor blood flow/ blood volume respond more favorably to chemoradiation therapy than patients with low blood flow/volume. [5][6][7][8][9] DCE-MRI studies yield a parameter called K trans , which is a measure of the first-order bidirectional volume transfer constant of contrast agent exchange between the intravascular plasma and tumor interstitium compartments. The pretreatment K trans , which reflects tumor perfusion/permeability, has been shown to predict nodal treatment response to chemoradiation therapy in patients with HNSCC.…”
mentioning
confidence: 99%
“…Increased tumor enhancement during early therapy has been found to correlate with tumor regression [11] and to be a favorable prognostic factor for local control [9]. However, at the completion of therapy, patients who achieved local control had significantly lower tumor signal enhancement than patients with local failure [13,15]. It has been suggested that the different correlations between signal enhancement and treatment outcome represent different phases of the tumor physiological response to radiotherapy [13].…”
Section: Discussionmentioning
confidence: 99%